Amanat dalam Novel Si Anak Badai Karya Tere Liye - Man Hakim; Ira Yuniati; Hesti Maharani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the message in the novel Si Anak Badai by Tere Liye. Data collection techniques using literature study techniques. The results of the study show that various messages are contained in the quote from the novel Si Anak Badai by Tere Liye. In the form of delivery of the mandate is divided into 2 ways, namely directly and indirectly. The most dominant form of delivery of the mandate is direct. In conclusion, there are 12 mandates in the novel Si Anak Badai by Tere Liye, namely, a) independent; b) mutual help; c) be responsible; d) filial piety to parents; e) forgive; f) loyal friends; g) the importance of education; h) be patient; i) honest; j) confident; k) brave; l) repay evil with good. Keywords: Mandate, Novel, Si Anak Badai by Tere Liye Novel